Genetic polymorphism in the NRF2 gene as a prognosis marker for cancer chemotherapy - Ishikawa, Toshihisa (Frontiers in Genetics, 2014)
NF-E2-related factor 2 (NRF2) is a transcription factor that controls the expression of a variety of antioxidant and detoxification genes. Accumulating evidence strongly suggests that NRF2 mediates cancer cell proliferation and drug resistance, as well. Single nucleotide polymorphism (SNP) -617C > A in the anti-oxidant response element-like loci of the human NRF2 gene play a pivotal role in the positive feedback loop of transcriptional activation of the NRF2 gene. Since the SNP (-617A) reportedly decreases the binding affinity to the transcription factors of NRF2/small multiple alignment format (MafK), the homozygous -617A/A allele may attenuate the positive feedback loop of transcriptional activation of the NRF2 gene and reduce the NRF2 protein level. As the consequence, cancer cells are considered to become more sensitive to therapy and less aggressive than cancer cells harboring the -617C (WT) allele. Indeed, Japanese lung cancer patients carrying SNP homozygous alleles (c. -617A/A) exhibited remarkable survival over 1,700 days after surgical operation (log-rank p = 0.021). The genetic polymorphism in the human NRF2 gene is considered as one of prognosis markers for cancer therapy.